(untitled) (Fiep Bulletin - online, 2016)
This article deals with the survey of the literature on body image and their constructs. We aimed to present the body image as a wrapped construct in different elements and variables that influence it, being noticeable that there is a problem that can have serious consequences for the training of adolescents, affecting the health, social relationships and the adoption of habits healthy and long-lasting physical activity and sport practices. The distance culturally idealized body affects the social dynamics in that the search for the framework on standards does not recognize boundaries, and such motivation exercised without due recognition of the diversity of physical constitutions that are present in the population, as well as the risks to physical health and psychological people. In this sense, understand the relationship between physical fitness levels with the self-perception of body image, should be cause for attention, social setting guided by inativismo obesity and sedentary behavior patterns. The analyzed studies showed theoretical support able to substantiate new research, highlighting the importance of programs developed in school.